Bedside ultrasound in the emergency department for reduction and radial manipulation of distal radial fractures. (25th June 2020) - Smiles, John P; Simonian, Marcus; Zhang, Michael; Digby, Shane; Vidler, Sam; Flannagan, Scott
Abstract : Distal radial fracture reduction is a common procedure in the ED. Previous studies have suggested that US‐guided reduction improves outcomes. We performed the first randomised controlled trial looking at this and found that US‐guided reduction of dorsally displaced, distal radius fractures in the ED, did not improve measured clinical outcomes. Abstract: Objective: Distal radial fracture reduction is a common procedure in the ED. Previous studies have suggested that ultrasound (US)‐guided reduction improves outcomes for patients who undergo manipulation and reduction of distal radial fractures in the ED. We aimed to investigate this with the first randomised controlled trial looking at US‐guided distal radial fracture reduction. Our primary objective was to compare rates of operative intervention between the study groups. Rate of re‐manipulation was compared as a secondary outcome. Methods: ED patients were prospectively randomised to either standard landmark guided or US‐guided closed reduction of distal radial fractures. The closed reductions were performed by senior emergency clinicians and the USs were performed by emergency physicians experienced in point‐of‐care US. Following reduction patients were managed equally and referred to the local orthopaedic service who were blinded to whether US was used to assist manipulation or not. This service decided on the need for re‐manipulation or operative intervention. Results: One hundred patients were enrolled and randomised equally into each cohort. We found no statistically significant difference between the control and intervention groups of our study. In the control group, 46% of patients underwent operative fixation, compared to 48% in the US‐guided group ( P = 0.36). Our secondary intervention of re‐manipulation in the ED or theatre following the initial reduction showed no statistically significant difference between the groups ( P = 1.0). Conclusion: US‐guided reduction of dorsally displaced, distal radius fractures in the ED setting, did not improve measured clinical outcomes.